ANALISIS IMPLEMENTASI PENDIDIKAN INKLUSIF DI SDN MARGOREJO 1 SURABAYA - Fitriyatun Nisa; Kayla Haifa Winarto; Rizkiyah; Lucky Zulkarnaen; Aiman Faiz (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Inclusive education is an educational approach that ensures all students, regardless of their abilities, receive equal learning opportunities. This study analyzes the implementation of inclusive education at SDN Margorejo 1 Surabaya. The research focuses on the challenges, strategies, and outcomes of inclusive education in this school. Data were collected through qualitative methods, including interviews with teachers, observations, and document analysis. The findings indicate that while inclusive education has been integrated into the school's curriculum, several obstacles such as limited resources, teacher preparedness, and parental involvement still hinder its effectiveness. The study suggests strategies for improving inclusive education implementation.